The Attempt of Location of Gender Studies within the Fundamental Metaphysical and Epistemological Attitudes to Reality. Some Tips for the Critics of Gender Studies - Kieliszek, Zdzisław (Studia Warmińskie, 2014)
The paper The Attempt of Location of Gender Studies within the Fundamental Metaphysical and Epistemological Attitudes to Reality. Some Tips for the Critics of Gender Studies has five parts. In the first part the author briefly presents the most important participants of the discussion about the gender identity. He also suggests that the definition of gender studies within the basic metaphysical and epistemological positions enables the identification of the most important directions, in which criticism of gender studies should follow. The second part is devoted to the characteristics of the basic metaphysical and epistemological attitudes to reality. Sequentially presented afterwards are metaphysical realism, metaphysical idealism, epistemological realism and epistemological idealism. The third part discusses the most important assumptions, arguments, and demands placed within gender studies. It also summons the typical representatives of gender studies. The fourth part shows the points of contact, tension and conflict between gender studies, and key metaphysical and epistemological positions. In the last part the author comes to the conclusion that gender studies seem to be a manifestation of the idealistic-metaphysical and realistic-epistemological attitude to reality. On this basis, he formulates five key indications that the critics of gender studies should take into account.